Antagonistic effects of biocontrol agents against Phytophthora infestans and growth stimulation in tomatoes - Kariuki, W.G.; Mungai, N.W.; Otaye, D.O.; Thuita, M.; Muema, E.; Korir, H.; Masso, C. (African Journals Online, 2020)
Late blight disease is a major cause of economic losses in tomato (Lycopersicon esculentum L.) production in eastern Africa. The objective of this study was to evaluate the efficacy of Trichoderma species in controlling late blight disease and their role on the growth of tomato. Trichoderma asperellum and T. harzianum were isolated from two commercial products containing the antagonistic species. Culture-based and molecular approaches, genomic DNA isolation and amplification, using ITS1 and ITS4 universal primers, and sequencing, were used to characterise the products. Trichoderma antagonistic effects against Phytophthora infestans (causative of tomato late blight) experiments were conducted in vitro and in the greenhouse. The greenhouse experiment had five treatments; namely, a negative control, Metalaxl-M, T. asperellum, T. harzanium and mixture of the two biocontrol agents, laid out in a randomised complete block design. The experiment was carried out for 12 weeks, with 3 weeks measurements intervals. Morphological and molecular characterisation confirmed the organism in most of the commercial products as T. harzianum and T. asperellum. An inhibiting action was observed on the P. Infestans mycelial growth, by the effect of T. asperellum (30.7%), and T. harzianum (36.9%).Trichoderma spp. suppressed late blight disease in the greenhouse experiment. These effects were specific to soil type, with the higher effectiveness realised in Ferralsols (27% disease severity) and least in Nitisols (36% disease severity). Trichoderma harzianum and T. asperellum resulted in higher above ground biomass of tomato of 31 and 19% increase over the control, respectively. There is potential of biocontrol agents in reducing P. infestans effects in tomatoes and in stimulating growth.